PEMANFAATAN TEKNOLOGI AI DALAM SISTEM PEMBELAJARAN BAHASA ARAB YANG ADAPTIF DAN RESPONSIF - Uswatul Jannah; Nurul Hanani (Study Program of Arabic Language Education (PBA), 2026)
Abstract This research article discusses the application of artificial intelligence (AI) technology in adaptive and responsive Arabic language learning systems. Given the complexity and challenges involved in language learning—particularly Arabic, which has a distinctive grammatical structure—AI technology offers a more efficient and personalized solution to these issues. By using an AI-based system, learning materials can be tailored to each student’s needs and abilities in real time. This article explores various AI technologies used in Arabic language learning, such as natural language processing (NLP), speech recognition, and machine learning, to create a system that is adaptive and responsive to students’ individual needs. This study aims to provide an overview of the potential of AI in enhancing the effectiveness of Arabic language learning, as well as the challenges that may be encountered in its implementation.